Behavioral optimization models for multicriteria portfolio selection - Mehlawat, M.K. (Yugoslav Journal of Operations Research; Vol 23 No 2 (2013): Vol. 23 No. 2, 2016)
In this paper, behavioral construct of suitability is used to develop a multi-criteria decision making framework for portfolio selection. To achieve this purpose, we rely on multiple methodologies. Analytical hierarchy process technique is used to model the suitability considerations with a view to obtaining the suitability performance score in respect of each asset. A fuzzy multiple criteria decision making method is used to obtain the financial quality score of each asset based upon investor's rating on the financial criteria. Two optimization models are developed for optimal asset allocation considering simultaneously financial and suitability criteria. An empirical study is conducted on randomly selected assets from National Stock Exchange, Mumbai, India to demonstrate the effectiveness of the proposed methodology.